Scanning electron microscopic study on sheep erythrocytes in experimental copper toxicity - Kumari, H; Srivastava, A K (The Indian Journal of Animal Sciences, 2011)
Ultrastructural study on erythrocytes of sheep in copper toxicity depicted poikilocytosis, anisocytosis, presence of spherocytes, keratocytes, burr cells and schistocytes, which can be used as presumptive diagnosis for copper toxicity.